Comparative evaluation of commercially valuable characters of cutting lettuce varieties (Lactuca sativa L.) in Kiev Oblast - В. Б. Кутовенко; Н. В. Тиха; К. Р. Попко (Plant Varieties Studying and Protection, 2015)
Purpose. Study of cutting lettuce varieties of Dutch breeding, determination of their morphological traits and commercially valuable characteristics. Methods. Field, laboratory, statistical. Results. Characteristics of five varieties of cutting lettuce of Dutch breeding were studied. It was established that the formation of marketable yield of lettuce leaves and their commercial quality largely depends on varietal features. Conclusions. Tested varieties are suitable for direct sowing on the field under conditions of Kiev Oblast. Time interval from mass germination to industrial ripeness was the shortest for Sirmay variety – 48–51 days. The largest number of leaves was recorded in Sirmay and Kitoniya varieties – 32,9 and 32,1 per plant respectively. The average weight of leave rosette was the highest in Sirman, Keaton and Karmesi varieties – 0,290, 0,266 and 0.207 kg respectively.